Estudio de factibilidad para el desarrollo de un sistema de información que maneje el control interno del Comercial "Carola". - Manobanda Lucong, Jaxcely Del Carmen (2022)
Internal Control is a process carried out by the Board of Directors, the management and the other members of an organization, in order to provide a reasonable degree of confidence in the achievement of objectives. The accounting, administrative and management profession is not left out of this change, since the quality of the information delivered to users for decision-making must be improved. Today, almost all organizations use computers in their daily business. The commercial company CAROLA, is a family business that has been maintained for 10 years, its main activity is the purchase and sale of corn and rice in the Urdaneta canton, where the need to increase productivity and efficiency is clearly seen in order to grow. A management information system can be a manual system or a computerized system using computers. Regardless of the type, GIS is designed to collect, input, process, store, and report data and information. The computerized administrative system involves the use of computers in the processing of administrative data into information to facilitate decision-making. The purpose of this case study is to analyze the feasibility for the development of an Information System for Internal Control that allows linking the three levels of organizational management. Qualitative methodology will be used to collect information. An interview will be used as a tool, which through a questionnaire of open questions will consider finding the problem in detail that exists in the piladora.